Masalah Keagenan Pada Struktur Kepemilikan Perusahaan Keluarga di Indonesia - Peny Cahaya Azwari (Department of Accounting-Faculty of Economic and Business (FEB), 2016)
Many things that are involved in the family ownership ranging from the formulation of the structure and distribution of ownership among the families involved; capitalization of capital; family coverage and control mechanisms within the company; policies to attract capital from outside the family or maintain dominance of family ownership, until the creation of capital-raising mechanism in a family environment to support the expansion and growth of the company. The ownership structure will determine the agency’s problems, which is whether that the dominant conflict occurred between the manager and the shareholder or between the controlling shareholder with the minority shareholders. The number of firms with family ownership in Indonesia provides positive and negative effects for development. On one hand, the conflict between the agent and the principal is very small compared with the company's non keluarga. This things is understandable because of the dominance and control of management decisions are determined by a majority of policy holders domination saham. It means that the policy decision still dominate by family ownership, which is it will affect that financial transparency